Pemberdayaan Santri Pondok Darussalam Adijaya Lampung Tengah Di Era Pandemi Melalui Budidaya Ayam Petelur - Prasetiawati, Eka; Banon Ferdiana; Abrori, M. Sayyidul; Hanif Amrulloh (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2023)
Central Lampung Regency has a layer farming business, one of which is at the Darussalam Islamic boarding school located in Adi Jaya village. The laying hen farming business plays an important role in the economy of the Darussalam Islamic boarding school. Thus, it is necessary to conduct research related to the cultivation of laying hens here. The objectives in this service are to find out the process of cultivating laying hens at the Darussalam Adi Jaya Islamic boarding school and to find out the marketing system of the laying hen farming business at the Darussalam Islamic boarding school in Central Lampung. The method used in the research is using the ABCD method. The implementation steps of laying hens cultivation in Darussalam Islamic boarding school include choosing good seeds, choosing feed always pays attention to two things, namely: knowledge of available feed substances, the amount of livestock needs for feed substances. Layer chicken cages in Darussalam boarding school are in the form of boxes or cages made of bamboo slats. Marketing system of layer chicken business in Darussalam boarding school in Adijaya Central Lampung. The owner of the layer chicken business provides a variety of chicken eggs ranging from small chicken eggs to large chicken eggs.